Effect of low velocity impact on deformation behavior of metallic pressure vessel - Farhood, N.H. (Asian Research Publishing Network, 2016)
The present study deals with the numerical investigations of aluminium pressure vessel behavior when impacted by spherical and blunt steel projectiles. One of the main causes of vessel rupture is the reduction of the vessel strength caused by external impact or material defect. The safety of the pressure vessel is vital because of its high working pressure which is more than 20 MPa and any untoward incidents must be avoided. Therefore, the main goal of this study is to predict the deformation and vessel strength behaviors for varying projectile shape, target thickness and impact velocity under low velocity impact conditions. In the modelling process, Johnson-Cook plasticity model was selected for the vessel material (Al 6061-T6) and direct impacts were subjected on the mid and dome vessel zones with varying parameters. The dynamic explicit analysis of the problem was carried out using ABAQUS finite element code. It has been concluded that, the target vessel exhibited lower impact resistance for blunt projectile compared to spherical projectile under the same impact loading conditions. Also, the damage which occurred in the dome vessel zone was greater than on the cylindrical area of the vessel, which leads to a specific design requirement in the dome zone. Finite element simulation results were compared with the numerical results in the literature and a good agreement was found. Â© 2006-2016 Asian Research Publishing Network (ARPN).